The addition rule for probabilities states: P(A or B) = P(A) + P(B) - P(AB) This is probably a dumb question but… if we’re give P(A) and P(B) can we just multiply them together to get P(AB) to finish the equation? I thought we could but according to the multiplication rule we can’t, unless their independent events. Is this true or can we multiply the two no matter what to find P(AB)? Thanks

If they are dependent P(AB) = P(A|B)*P(B) If they are independent P(AB) = P(A)*P(B) If mutually exclusive, P(AB) = 0